Misfolding, Aggregation, and Disordered Segments in c-Abl and p53 in Human Cancer - de Oliveira, Guilherme A. P.; Rangel, Luciana P.; Costa, Danielly C.; Silva, Jerson L. (Frontiers in Oncology, 2015)
The current understanding of the molecular mechanisms that lead to cancer is not sufficient to explain the loss or gain of function in proteins related to tumorigenic processes. Among them, more than 100 oncogenes, 20-30 tumor suppressor genes and hundreds of genes participating in DNA repair and replication have been found to play a role in the origins of cancer. The phosphorylation of serine, threonine, or tyrosine residues is a critical step in cellular growth and development and is achieved through the tight regulation of protein kinases. The deregulation of kinase control mechanisms has disastrous consequences, often leading to gains of function, cell transformation and cancer. The c-Abl kinase protein is one of the most studied targets in the fight against cancer and is a hotspot for drug development because it participates in several solid tumors and is the hallmark of chronic myelogenous leukemia. Tumor suppressors have the opposite effects. Their fundamental role in the maintenance of genomic integrity has awarded them a role as the guardians of DNA. Among the tumor suppressors, p53 is the most studied. The p53 protein has been shown to be a transcription factor that recognizes and binds to specific DNA response elements and activates gene transcription. Stress triggered by ionizing radiation or other mutagenic events leads to p53 phosphorylation and cell cycle arrest, senescence or programmed cell death. The p53 gene is the most frequently mutated gene in cancer. Tumor-associated p53 mutations often lead to the loss of protein function, but recent investigations have also indicated gain-of-function mutations. The prion-like aggregation of mutant p53 is associated with loss-of-function, dominant-negative and gain-of-function effects. Here, we review the recent insights into the protein structure and function of the c-Abl and p53 proteins that will provide us guidance to understand the loss and gain of function of these misfolded tumor-associated proteins.